Consumer Legal Remedies for Delayed Ticket Refunds from the Perspective of the Consumer Protection Law and Islamic Law (A Study of the Day6 World Tour Indonesia Community) - Siti Inayatul Hasanah (Program Studi Hukum Ekonomi Syariah Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The entertainment industry, particularly music concert organization, involves a legal relationship between promoters and consumers. The change of venue for the Day6 Indonesia World Tour concert by PT Melania Citra Permata (Mecimapro) resulted in refund requests from consumers. However, 1,722 consumers with a total refund value of Rp4.6 billion had not received their funds despite promises since April 2025, creating legal uncertainty and material losses. This study analyzes consumer legal remedies due to refund delays and examines them from the perspectives of Consumer Protection Law and Islamic Law, using an empirical legal research method with a qualitative approach. The results show consumers pursued remedies gradually from individual efforts via refund forms and social media, to collective actions through My Day Berserikat, including mediation facilitated by BPKN and the Ministry of Trade, and hearings with YLKI. Legal certainty remains unachieved, opening the possibility of litigation. From the Islamic law perspective, the delay contradicts contract fulfillment principles, prohibition of injustice, and protection of property (ḥifẓ al-māl) within maqāṣid al-sharī'ah.